IMPLEMENTASI PEMBELAJARAAN KONTEKSTUAL DENGAN STRATEGI PERCOBAAN SEDERHANA BERBASIS ALAM LINGKUNGAN SISWA KELAS X - Lilia, Lita; Widodo, Antonius Tri (Jurusan Kimia, Fakultas Matematika dan Ilmu Pengetahuan Alam, Universitas Negeri Semarang, 2014)
The limitations of the tools and materials made practicum in school is not performing well, so it requires a simple experimental strategy. This study aims to determine the differences of outcomes in using contextual learning with a simple experimental strategy and the magnitude of mastery learning subject matter of redox reactions in a high school in Tegal. The population of this study was all class X at the high school. The sampling technique used was cluster random sampling, obtained X-2 as an experimental class using the strategy of implementation of contextual learning environments on simple experiments and X-3 as a control class using the expository method. The study design was a posttest only control group design. After learning by using the contextual method, a posttest were performed in the experimental and control class. Statistical test used are the test for normality, equality of two variances, the difference between two average and mastery learning. The average grade of experimental class posttest 80.86 and control class 73.70. In the hypothesis test, obtained t Â 3.501 greater than 1.993, with 5% significance level and 74 degrees of freedom. It means that the average grade of cognitive achievement is better than the control experiment, so it can be concluded thah the implementation of contextual learning with a simple experimental strategy based environments in class X gives a positive difference to the learning outcomes of the subject matter of the redox chemistry in class X.Keywords:A Simple Experiment Based Environments, Contextual Learning